Effects of Waste Cooking Oil on the Antiageing Ability of Bitumen - Shobhit Jain; Sairam Dabbiru; Anush K. Chandrappa (Advances in Civil Engineering)
Ageing is considered one of the significant issues faced by bituminous mixtures. The short-term ageing phase involves a significant rise in the bitumen’s viscosity, which may lead to early raveling and cracking. Antiageing additives are prescribed to reduce the effects of short-term ageing. However, most antiageing additives have detrimental health effects and also affect water quality. In recent times, waste cooking oil (WCO) has gained attention as a potential antiageing additive considering its peptizing ability. In this study, the antiageing ability of WCO is investigated considering the rheological and chemical parameters of the bitumen (binder). The rheological test included oscillation, frequency sweep, and multiple stress creep recovery (MSCR). The chemical test included the extraction of asphaltene from the bitumen. PG 64-10 and VG30 binders were short-term aged and modified with 3.0 and 5.0% WCO, respectively. The master curves indicated the presence of optimum WCO content for the binders, where the WCO short-term aged modified binders overlapped with that of unaged binders. The Burger model fitted for the creep phase of the bitumen indicated a significant increase in the viscous strain when the WCO addition exceeded the optimum value. The ageing indices based on rheological and chemical parameters depicted an excellent correlation. The optimum values of WCO based on rheological, chemical, and ageing indices were found to be in tandem. Overall, WCO has the potential to function as an antiageing additive, and the optimum value should be identified meticulously, as adding beyond the optimum may lead to permanent deformation.